The invasive investigation of INOCA in the coronary catheterization lab - Sonya N. Burgess; Mamas A. Mamas (American Heart Journal Plus, 2024)
Over half of all patients with angina have no angiographically demonstratable obstructive coronary disease, with a significant proportion of these patients having undiagnosed microvascular dysfunction and/or vasospastic angina. In chronic coronary syndrome, ischemia with non-obstructive coronary artery disease (INOCA) often remains undiagnosed, or uninvestigated. INOCAmay occur due to vasospastic angina and microvascular dysfunction and require invasive assessment in the coronary catheterization lab. To evaluate INOCA coronary flow reserve (CFR) and the index of microcirculatory resistance (IMR) are used to assess microvascular dysfunction before acetylcholine provocation testing for coronary spasm. This review provides an overview of the invasive investigation of INOCA in the coronary catheterization lab for patients with angina to be optimally managed.